Pengaruh spiritual emotional freedom technique (SEFT) terhadap skor kecemasan narapidana - Annas, Grandis Dwi; Estria, Suci Ratna; Linggardini, Kris; Muzaenah, Tina (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Anxiety is a feeling of worry, discomfort, uncertainty, or fear that arises from real or perceived events. It is often characterized by vague fears, accompanied by feelings of helplessness, isolation, and insecurity. Anxiety is a common mental health problem that can affect anyone, including their superiors. Anxiety experienced by revenge can stem from various events and experiences that occur during the isolated period. Several factors contribute to the development of anxiety disorders, including compensation, including age, length of sentence, time remaining before custody, and level of family and social support from the community. Purpose: To determine the effect of spiritual emotional freedom technique (SEFT) on anxiety scores of prisoners. Method: Quantitative research with pre-experimental design using one-group pretest-posttest methodology. This study was conducted on prisoners at Class IIB Purbalingga Penitentiary who had served more than four years. The sampling method used total sampling because the population was less than 100. The total number of participants in this study was 42 prisoners. This study used the Zung Self Anxiety Rating Scale (ZSAS), a questionnaire to measure anxiety. Results: The anxiety scores of the participants were at a mild level of 35.7%, a moderate level of 47.6%, and a severe level of 16.7%. The results of the analysis showed that there was a significant difference in anxiety scores from SEFT therapy in participants before and after the intervention with a p value of 0.001 ≤ ɑ (0.05) which indicated a decrease in anxiety scores before and after the intervention. Conclusion: There was an effect before and after the SEFT intervention with a p value = 0.001 and there was a difference in the decrease in score of 29.6 which shows that SEFT had an effect in reducing participants' anxiety scores. Keywords: Anxiety; Prisoners; Spiritual Emotional Freedom Technique (SEFT). Pendahuluan: Kecemasan adalah perasaan khawatir, tidak nyaman, tidak pasti, atau takut yang muncul dari peristiwa nyata atau yang dipersepsikan. Sering kali ditandai dengan ketakutan yang samar, disertai perasaan tidak berdaya, terasing, dan tidak aman. Kecemasan merupakan masalah kesehatan mental yang umum dan dapat memengaruhi siapa saja, termasuk narapidana. Kecemasan yang dialami oleh narapidana dapat berasal dari berbagai peristiwa dan pengalaman yang dihadapi selama masa penahanan. Tujuan: Untuk mengetahui pengaruh spiritual emotional freedom technique (SEFT) terhadap skor kecemasan narapidana. Metode: Penelitian kuantitatif dengan desain pra-eksperimental menggunakan metodologi one-group pretest-posttest. Studi ini berkaitan dengan narapidana di Lembaga Pemasyarakatan Kelas IIB Purbalingga yang telah menyelesaikan lebih dari empat tahun masa hukuman. Metode pengambilan sampel menggunakan total sampling karena ukuran populasi kurang dari 100. Jumlah total partisipan dalam penelitian ini adalah 42 narapidana. Studi ini menggunakan Zung Self Anxiety Rating Scale (ZSAS) yaitu kuesioner untuk mengukur kecemasan. Hasil: Skor kecemasan partisipan berada dalam tingkat ringan sebanyak 35.7%, tingkat sedang 47.6%, dan berat 16.7%. Hasil analisis menunjukkan bahwa ada perbedaan skor kecemasan yang signifikan dari terapi SEFT terhadap partisipan sebelum dan sesudah intervensi dengan p value 0.001 ≤ ɑ (0.05), menunjukkan terdapat penurunan skor kecemasan sebelum dan sesudah intervensi. Simpulan: Terdapat pengaruh sebelum dan setelah dilakukan intervensi SEFT dengan p value = 0.001, dan terdapat selisih penurunan skor sebanyak 29.6, menunjukkan bahwa SEFT berpengaruh dalam menurunkan skor kecemasan partisipan. Kata Kunci: Kecemasan; Narapidana; Spiritual Emotional Freedom Technique (SEFT).